Design of Reversible Logic Gates for Digital Applications - Saravanan, M.; Suresh Manic, K.; Umasuresh; Aravind CV; John Wiselin (Asian Journal of Electrical Sciences, 2013)
Recent applications of quantum computing is the design and evaluations on the reversible logic technology. The digital systems widely utilize the code conversion technology in enhancing the data security and also minimize the required hardware. This nano-metric technology is high prolific in digital systems as it minimize the power consumption in logic circuits. This paper proposes the reversible logic design for such a code conversion including the binary to gray code, gray to binary code, BCD to excess 3 codes, excess 3 to BCD code.